Pengaruh Iklan dan Potongan Harga terhadap Keputusan Pembelian Konsumen Marketplace Tokopedia di Kota Malang - Achmad Rizky; Abdul Waris (Universitas 17 Agustus 1945 Semarang, 2024)
Tokopedia, as a marketplace with the highest number of website visitors in Indonesia, certainly has advantages that become its appeal. Advertising and price discounts are factors that influence consumers to make purchasing decisions. This research is conducted to determine the influence of advertising and price discounts on the purchasing decisions of Tokopedia marketplace consumers in Malang City. This research was quantitative research using two independent variables, advertising and price discounts, and purchasing decisions as the dependent variable. The population of this study consisted of consumers who made purchases on the Tokopedia marketplace in Malang City. The data were collected by distributing questionnaires to 100 respondents using purposive sampling technique. The analysis method used was multiple linear regression analysis and hypothesis testing.In this research, it was found that advertising had an influence on purchasing decisions. Price discounts also had an influence on purchasing decisions. Advertising and price discounts together had an influence on purchasing decisions of Tokopedia marketplace consumers in Malang City. In multiple regression analysis, it was found that price discounts had a more dominant influence on the purchasing decisions of Tokopedia marketplace consumers in Malang City.Based on the results of this research, it can be concluded that advertising and price discounts have an influence on consumer purchasing decisions. Tokopedia is expected to provide the latest innovations for its advertising to emotionally engage the audience and encourage them to make purchases on the Tokopedia marketplace. Additionally, it is hoped that Tokopedia will increase the intensity and quantity of offering price discounts through campaigns that can attract consumer attention.